2021
DOI: 10.1021/acsabm.1c00289
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Aggregation of a Perylene-Derived Probe for Near-Infrared Fluorescence Imaging and Phototherapy

Abstract: The design and synthesis of water-soluble phototherapeutic agents with near-infrared (NIR) fluorescence emission is highly desirable for cancer diagnosis and treatment. Here, we report the construction of an amphiphilic perylene-derived photosensitizer, AP. AP shows NIR emission with large Stokes shift (130 nm) and high 1O2 quantum yield (22%). It can self-assemble into nanoparticles in aqueous solution with quenched fluorescence emission due to aggregation-induced quenching. Upon membrane anchoring, AP is abl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…By modifying the structure of perylene molecule, a washing-free CM staining NIR probe will be constructed based on disassembly light-up fluorescence strategy. For example, in 2021, Yu et al developed an amphiphilic NIR perylene derivative (probe 12 ) with a hydrophilic quaternary ammonium functional group and a hydrophobic long alkyl chain ( Figure 12 A) [ 69 ]. In aqueous solution, this probe could self-assemble into nanoparticles without fluorescence emission.…”
Section: Nir Molecular Probes For CM Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…By modifying the structure of perylene molecule, a washing-free CM staining NIR probe will be constructed based on disassembly light-up fluorescence strategy. For example, in 2021, Yu et al developed an amphiphilic NIR perylene derivative (probe 12 ) with a hydrophilic quaternary ammonium functional group and a hydrophobic long alkyl chain ( Figure 12 A) [ 69 ]. In aqueous solution, this probe could self-assemble into nanoparticles without fluorescence emission.…”
Section: Nir Molecular Probes For CM Imagingmentioning
confidence: 99%
“…( E ) Tumor volume changes of the 4T1 tumor-bearing mice under different treatments. Copyright 2021 American Chemical Society [ 69 ].…”
Section: Figures and Schemementioning
confidence: 99%
“…Yang et al reported an amphiphilic perylene derivative AIE-PSs named AP ( ϕ Δ = 0.22, methylene blue as reference) which is capable of cell-membrane-targeting [ 44 ]. AP could form nanoparticles by self-assembly in an aqueous solution and decompose into free monomeric molecules after membrane anchoring ( Figure 4 ).…”
Section: Organelle-targeting Aie-pdtmentioning
confidence: 99%
“…Perylene diimide (PDI) derivatives exhibited tremendous potential as a PS in PDT applications due to their excellent thermal and photostability, high extinction coefficients, low dark toxicity, and significant singlet oxygen quantum yield. , Structurally, PDI is a rigid hydrophobic aromatic polycyclic molecule, and its π–π aggregation has limited its biological application. , Interestingly, by conjugating PDIs with biological molecules such as amino acids and short peptide sequences, soluble structures are created with unique optical, physicochemical, and structural properties, which could modulate the self-assembly of PDI for different biomedical applications. Several groups have reported using conjugated PDI derivatives due to their stability, phototoxicity, and biocompatibility properties in PDT …”
Section: Introductionmentioning
confidence: 99%
“…29−31 Several groups have reported using con-jugated PDI derivatives due to their stability, phototoxicity, and biocompatibility properties in PDT. 32 Hydrogels have received increasing attention as promising nonimmunogenic delivery vehicles for enhancing the biological activity of PSs in PDT with the inherent exclusive characteristics of low toxicity, biodegradability, hydrophilic matrix, and drug-local and controlled diffusion properties. 33,34 Hydrogels are three-dimensional (3D) cross-linking hydrophilic polymer chains that absorb significant amounts of water while maintaining self-organization.…”
Section: Introductionmentioning
confidence: 99%